Kewenangan Aparat Kepolisian dalam Pengawalan Konvoi Kendaraan Bermotor Berukuran Besar di Jalan Raya - I Made Adi Putra; I Nyoman Putu Budiartha; I Ketut Sukadana (Warmadewa Press, 2020)
It is common for a large motorbike convoy to cause accidents, both between large motorbike riders and other vehicle riders. This is due to the fact that the speed of the large-sized motorbikes itself can be said to be quite fast, coupled with the behavior of some of these riders who sometimes like to run red lights and put aside the traffic signs, which often results in accidents. Based on this factual background, the legal issues examined in this study are: What is the authority of the police in escorting large motorbike convoys and what is the responsibility of the police in implementing the convoy when accident victims occur on the road. The type of research used in this research is normative legal research. The results of this research are that the authority of the police apparatus in providing escort for large motorbike convoys is the provision of Article 14 letters a and 18 paragraph (1) of Law no. 2 of 2002 concerning the National Police of the Republic of Indonesia and Article 12 letter e of Law No. 22 of 2009. These provisions basically constitute the authority of the police apparatus to carry out the regulation, guarding, escort and patrol of community and government activities as needed, and to give the authority to act according to their own judgment in the public interest. The responsibility of the police is to carry out the convoy in the event of a victim of an accident on the highway in order to maintain order and ensure security, safety, orderliness and smoothness of road transportation.